SARS-CoV-2 humoral immune responses in convalescent individuals over 12 months reveal severity-dependent antibody dynamics - Nadia Siles Alvarado; Maisey Schuler; Cole Maguire; Dzifa A. Amengor; Annalee W. Nguyen; Rebecca E. Wilen; Jacob Rogers; Sam Bazzi; Blaine Caslin; Christopher DiPasquale; Melissa Abigania; Eric Olson; et al. (Communications Medicine)
Abstract Background Defining the kinetics of SARS-CoV-2 antibody responses is critical for informing the management of reinfections, vaccinations, and therapeutics of Coronavirus disease 2019 (COVID-19). Methods Using four antibody assays, we evaluated antibody titers against SARS-CoV-2 nucleocapsid (N), spike (S), and receptor binding domain (RBD) in 98 convalescent participants with varying COVID-19 disease severities (asymptomatic, mild, moderate or severe) at 1, 3, 6, and 12-months post-SARS-CoV-2-positive PCR and in 17 non-vaccinated, non-infected controls. Results Increasing acute COVID-19 disease severity correlates with higher anti-N and anti-RBD titers throughout 12 months post-infection. Anti-N and anti-RBD titers decline over time in all participants, except for increased anti-RBD titers post-vaccination, with hospitalized participants exhibiting faster decay rates. Less than 50% of participants retain anti-N titers above controls at 12 months, with non-hospitalized participants falling below controls sooner. Nearly all participants maintain anti-RBD titers above controls for 12 months, suggesting long-term protection against severe reinfections. Nonetheless, by 6 months, few participants retain >50% of their initial 1-month anti-N or anti-RBD titers. Notably, vaccine-induced anti-RBD titers are higher in non-hospitalized participants. Lastly, early convalescent titers correlate with age but not with Post-Acute Sequelae of SARS-CoV-2 infection (PASC) status or steroid use. Conclusion Hospitalized participants initially develop higher anti-SARS-CoV-2 antibody titers that decline faster relative to non-hospitalized participants. While anti-N titers fall below control levels in some participants, anti-RBD titers remain above controls over 12 months, demonstrating long-lived antibody responses known to protect against severe disease. These findings advance our understanding of COVID-19 antibody dynamics.